2004
DOI: 10.1144/1354-079303-616
|View full text |Cite
|
Sign up to set email alerts
|

Heat flow in the Vøring Basin, Mid-Norwegian Shelf

Abstract: In situ temperature and heat flow were determined in 1994 at 159 sites, grouped into 66 clusters between latitude 65 N and 67 30' N at water depths from 669 m to 1464 m. The mean of all cluster heat-flow measurements conducted in this survey was 58.5 mW m 2 , with a standard error of 4.40 mW m 2 . The mean heat flow from IKU well data for the Trøndelag Platform is 56.2 6.65 mW m 2 . Shorter wavelength heat-flow variations appear to be controlled structurally and can be explained by sedimentation and thermal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 32 publications
3
26
1
Order By: Relevance
“…Ritter et al (2004) made some simple 1-D models in order to interpret new heat flow measurements from the Vøring area. Ritter et al (2004) concluded that neither crustal thinning, underplating nor sill intrusion, within the last 50 My, would have a measurable effect on present day heat flow.…”
Section: Introductionmentioning
confidence: 99%
“…Ritter et al (2004) made some simple 1-D models in order to interpret new heat flow measurements from the Vøring area. Ritter et al (2004) concluded that neither crustal thinning, underplating nor sill intrusion, within the last 50 My, would have a measurable effect on present day heat flow.…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding surface heat flow is q s = λ · ∂ T/∂z = 6.5 mW m −2 when the heat conductivity is λ = 2.5 W m −1 K −1 . This maximum additional heat flow from underplating is 10% of a typical value for the present day surface heat flow in Vøring area [27].…”
Section: Surface Heat Flowmentioning
confidence: 70%
“…This section looks at the possible thermal impact from magmatic underplating for the three scenarios of the extension history reported by Wangen et al [41]. The rock properties used in the simulations are found in Appendix D. The present study does not cover uncertainties in the input data but uses standard data to obtain a surface heat flow that is in accordance with the heat flow measurements collected by Ritter et al [27]. Figure 9a shows the same transect as in Wangen et al [41], where the lithosphere is plotted right after emplacement of the magma.…”
Section: Vøring Heat Flow From Underplatingmentioning
confidence: 97%
“…In very broad terms, the representative models for the southern part of the area (Fig. 5a-f ) appear to bracket the typical heat flows observed there, whereas the more extensive heat-flow data available for the Norwegian margin and, in particular, the Vøring Basin (Sundvor et al 2000;Ritter et al 2004) suggest a thermal state closer to the warm models than the cool models.…”
Section: Construction Of Yield Strength Envelopesmentioning
confidence: 81%
“…5i, j). With higher heat flows, which appear more likely in this area (Sundvor et al 2000;Ritter et al 2004), the predicted temperatures within this layer move out of the stability zone for lizardite (note the depths of the 300 and 4008C isotherms in Fig. 5j), so the likelihood of this being a source of weakening is reduced.…”
Section: Comparison Of the Yield-strength Envelopesmentioning
confidence: 97%